Solute segregation assisted nanocrystallization of a cold-rolled Mg–Ag alloy during annealing. (1st March 2020) - Xiao, L.R.; Chen, X.F.; Cao, Y.; Zhou, H.; Ma, X.L.; Yin, D.D.; Ye, B.; Han, X.D.; Zhu, Y.T.
Abstract: Refining grains to nanoscale has been a challenge, especially for materials with low-melting points and poor ductility, such as Mg alloys. Here we report a novel mechanism of nanocrystallization assisted by solute segregation, by which a nanocrystalline Mg-Ag alloy was produced by moderate cold rolling (∼55% strain) followed by low-temperature annealing. Specifically, during cold rolling non-basal 〈 c   +   a 〉 dislocations were activated to form dislocation cells walls, which were pinned by Ag segregation, and transformed into boundaries of nanocrystalline grains during annealing. Graphical abstract: Image, graphical abstract